Determinants of unemployment rate in selected ASEAN countries / Zulaikha Sulaiman @ Ismail - Sulaiman @ Ismail, Zulaikha (2017)
This study investigate the factors that influence unemployment rate (UR) using selected ASEAN countries which are Malaysia, Indonesia, Philippines, Thailand and Singapore as a case of study, with specific attention on population (POP), inflation rate (IR), and foreign direct investment (FDI).The time period examined is from 1982 to 2016 and all the tests are conducted based on yearly data which is containing a total number of 175 yearly data observations. Specifically, this study aimed to address the following: (1) To determine the most significant factors that influence unemployment rate in selected ASEAN countries; (2) To examine the relationship between populations, Inflation rate, foreign direct investment, and unemployment rate. POLS regression, Panel Data Analysis, Multicollinearity Test, Heteroscedasticity Test and Hausman Fixed Test constituted the analytical methods. From FEM regression, population (POP) was determined to have a positive and significant relationship with unemployment rate (UR) whereas foreign direct (FDI) was observed to have negative and significant relationship with unemployment rate (UR). However, inflation rate (IR) was found to have negative and an insignificant relationship with unemployment rate (UR). The results provided some useful insights into the effects of macroeconomic factors on the unemployment rate in selected ASEAN countries